2020
DOI: 10.1186/s12891-020-3150-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and location of heterotopic ossification following hip arthroscopy

Abstract: Background:We investigated the incidence and location of heterotopic ossification (HO) following hip arthroscopy. Methods: This retrospective study enrolled 327 patients who underwent hip arthroscopy from January 2010 to December 2015. From this cohort, we extracted an HO group with simple radiographs or three-dimensional computed tomography (3D CT). Findings consistent with HO were classified according to the Brooker classification aided with 3D CT for the location of HO. The indication for revision arthrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…42,81 Although widely studied, the exact mechanism by which HO develops has not yet been well established. 3,27,81,88 A suggested model is that the interaction between the injured periosteum and necrotic or damaged muscle may induce periosteal bone production. 2 Additionally, direct trauma to the soft tissue causes the release of bone morphogenic protein 2, which upregulates the release of inflammatory markers; this results in the recruitment of immune cells and the initiation of processes essential for nerve remodeling, fibroproliferation, and angiogenesis, which are necessary for HO formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…42,81 Although widely studied, the exact mechanism by which HO develops has not yet been well established. 3,27,81,88 A suggested model is that the interaction between the injured periosteum and necrotic or damaged muscle may induce periosteal bone production. 2 Additionally, direct trauma to the soft tissue causes the release of bone morphogenic protein 2, which upregulates the release of inflammatory markers; this results in the recruitment of immune cells and the initiation of processes essential for nerve remodeling, fibroproliferation, and angiogenesis, which are necessary for HO formation.…”
Section: Resultsmentioning
confidence: 99%
“…69 In a series of 327 patients, a recent study found 14 cases (4.28%) of radiographically confirmed HO after hip arthroscopy, with 12 patients asymptomatic at the last follow-up. 88 In most cases, HO was in the central area of the arthroscopic portals or capsulotomy. Two patients with Brooker grade 2 disease required revision hip arthroscopy to excise symptomatic HO.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…51 These complications are uncommon in arthroscopy. 52 Maqungo et al reported a prospective case series of ten patients treated with surgical hip dislocation for removal of retained intraarticular bullets in the hip. 53 In this series, average blood loss was noted to be 255 ml, wound infection in one patient was noted following surgery, and average length of stay was noted to be 12.8 days for these 10 patients.…”
Section: Discussionmentioning
confidence: 99%